Multimorbidity and statin prescription for primary prevention of cardiovascular diseases: A cross-sectional study in general practice in France - Onaisi, Racha; Dumont, Roxane; Hasselgard-Rowe, Jennifer; Safar, David; Haller, Dagmar M.; Maisonneuve, Hubert (Frontiers in Medicine, 2023)
Background: Statins are a first line, evidence-based yet underprescribed treatment for cardiovascular primary prevention. In primary care settings, multimorbidity is a complex situation which makes it difficult to apply prevention guidelines. Aim: To assess the associations between multimorbidity and prescription of statins in accordance with the 2016 ESC recommendations (“appropriate prescription”), and to identify the factors and conditions associated with these prescriptions. Design and Setting: Cross-sectional prospective study in the French region of Rhône-Alpes among 40 general practitioners and their patients. Method: We examined the association between appropriate statin prescription and several patient characteristics, including multimorbidity, using multivariate logistic regression models. Results: Between August 2017 and February 2019, 327 patients were included in the study. Seventy-four (22.6%) were on statin medication and 199 (60.9%) exhibited multimorbidity, defined as ≥ 2 diseases. Only 22.5% of eligible patients were prescribed statins for primary prevention. Diabetes was most strongly associated with appropriate statin prescription (aOR 8.10, CI95: 3.81-17.80). Multimorbidity was not associated with appropriate statin prescription (aOR 1.31, CI95: 0.54-3.26), except in the presence of diabetes which defined diabetic multimorbidity (aOR 10.46, CI95: 4.87-23.35). Conversely, non-diabetic multimorbidity was associated with lower odds of being appropriately prescribed a statin (aOR 0.26, CI95: 0.12-0.56). Conclusion: Multimorbidity, in itself, does not seem to be a determinant factor for appropriate statin prescription. The latter appears to be determined by a patient’s type of multimorbidity, especially the presence or not of diabetes. Differentiating between diabetic and non-diabetic multimorbidity may be a pragmatic way for GPs to improve primary prevention in a patient-centered and shared decision-making approach.